The Role of IR in Pediatric Pain and Palliation - Leshen, Michael L.; Hawkins, C. Matthew (Seminars in Interventional Radiology, 2025)
Pediatric chronic pain is a significant problem that is often underreported and therefore not always adequately addressed. Causes include anatomic variants, trauma, local inflammation, and malignancy. Nerve blocks and cryoneurolysis can aid as an adjunct to pain management for these patients and significantly improve their quality of life. This article will describe specific procedures in which interventional radiology can aid in several specific procedures for pediatric pain management: splanchnic cryoneurolysis, sphenopalatine ganglion nerve block/cryoneurolysis, inferior alveolar nerve block, intercostal cryoneurolysis, and cryoablation of painful bone metastases, notably in the setting of metastatic sarcoma.
Keywords: interventional radiology; pediatric; palliation; nerve block; cryoneurolysis